2014
DOI: 10.1091/mbc.e14-01-0042
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine uptake is the major effector of extracellular ATP toxicity in human cervical cancer cells

Abstract: Cervical cancer cells respond to high extracellular ATP. There is cooperation between ATP and its metabolites with regard to cytotoxicity, with adenosine necessary, but not sufficient, to induce cell death in the whole population of cells, which is significant in the context of cancer therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 40 publications
4
32
0
5
Order By: Relevance
“…By using ENTs inhibitor, S-(4-nitrobenzyl)-6-thioinosine (NBTI), our results showed that NBTI was able to rescue CCA from adenosine (Figures 3 and 4). This suggested the transporter-dependent cancer inhibition, similar to what has previously been reported in colon and cervical cancers [3,4]. Since the activity of ENTs was required in CCA cell inhibition by adenosine, intracellular level of adenosine in CCA cells after adenosine treatment was examined.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…By using ENTs inhibitor, S-(4-nitrobenzyl)-6-thioinosine (NBTI), our results showed that NBTI was able to rescue CCA from adenosine (Figures 3 and 4). This suggested the transporter-dependent cancer inhibition, similar to what has previously been reported in colon and cervical cancers [3,4]. Since the activity of ENTs was required in CCA cell inhibition by adenosine, intracellular level of adenosine in CCA cells after adenosine treatment was examined.…”
Section: Discussionsupporting
confidence: 78%
“…Adenosine was shown to signal through its receptors on the cell membrane [1,2]. In addition, adenosine was reported to be transported into cytoplasm via equilibrative nucleoside transporters (ENTs) [3][4][5]. There are four subtypes of adenosine receptors in mammalian cells, namely A1, A2a, A2b and A3 [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, both studies showed that the addition of activated T-cells to their culture system allowed the generation of Ado from ATP due to the high CD39 expression on activated T-cells, suggesting a co-operative functional activity between MSCs and activated T-cells in the inflammatory microenvironment to generate Ado from ATP released in the damaged tissue [23, 24]. Therefore, our results suggest that CeCa-MSCs in association with cervical tumor cells, which according to Maldonado et al [49] and Mello et al [50] are part of the tumor microenvironment in CeCa, can contribute significantly to the generation of Ado in the presence of high levels of ATP [49, 50]. …”
Section: Discussionsupporting
confidence: 52%
“…In cervix cancer cells, in turn, the toxicity of extracellular ATP is mediated mainly by the uptake of extracellular adenosine and AMPK activation. In this model, autophagy plays a cytotoxic role and the cotreatment with Ca 21 chelator EGTA does not suppress ATP-induced cell death (Mello et al, 2015). Together, these data suggest that the role played by Ca 21 in the response to extracellular ATP may depend on the model of study.…”
Section: Autophagy Ca 21 and Cancermentioning
confidence: 76%